PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP HARGA SAHAM DENGAN SIZE PERUSAHAAN SEBAGAI PEMODERASI - Nik Amah; Purweni Widhianningrum; Hestin Mawarni (Jurnal Penelitian LPPM (Lembaga Penelitian dan Pengabdian kepada Masyarakat) IKIP PGRI MADIUN, 2014)
This study aimed to examine the effect of the Corporate Social Responsibility disclosure on stock prices and find out if the firm's size is able to be variable moderating the influence of CSR disclosure to the stock price. The study was conducted at a mining companies listed on the Indonesia Stock Exchange 2011-2013. The samples using purposive sampling and obtained a sample of 10 companies with annual report data during 2011-2013 were 30 reports. Data analysis used thedifference absolute value. The test results show that corporate social responsibility disclosure has significant positive effect on stock prices. The testing of difference absolute value shows that the firm's size is not a moderating variable to influence corporate social responsibility disclosure to the stock price.